RNA N6‐methyladenosine connects YTHDF3 and LOXL3 to promote melanoma metastasis - Mamta B Nirmal; Tommy V. Vo (Wiley, 2022)
Abstract N6‐methyladenosine (m6A) modifications of RNAs are associated with diverse biological processes in normal and cancer cells. In melanoma cancers, mutations in genes that function in the writing or erasure of RNA m6A have been shown to affect cancer progression and metastasis. More recently, Shi et al. find that a protein which binds to the m6A modification, called YTHDF3, is widely overexpressed in melanoma cell lines and patient samples. Through multi‐omics and targeted RNA analyses, they uncover a novel YTHDF3‐LOXL3 axis which contribute to in vitro melanoma invasion and in vivo metastasis. Here, we discuss these findings and highlight several possible new and exciting research directions stemming from this research.